A semi greedy soft real-time multiprocessor scheduling algorithm - Alhussian, H. (Institute of Electrical and Electronics Engineers Inc., 2014)
Soft real-time systems are systems that can tolerate deadline misses but at the expense of degradation in quality of service. Many of the Scheduling algorithms used to schedule real-time tasks in a multiprocessor soft real-time systems are extended from their uniprocessor counterparts such as Global Earliest Deadline First (G-EDF) and Least Laxity First (LLF). However such algorithms when extended to real-time multiprocessor scheduling achieve low schedulability rates. In this paper, we present an efficient real-time multiprocessor scheduling algorithm that achieves high schedulability rates compared to currently existing algorithms. Unlike the current algorithms which are known to be greedy, our proposed algorithm uses a semi-greedy criteria to schedule tasks. The simulation showed that the proposed algorithm misses few deadlines as well as achieves high schedulability rates compared to currently existing algorithms. Â© 2014 IEEE.